(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
Cultural heritage is a concept that has been constantly resignified. Its rules of protection are related to the new theoretical postulates acquired. The international organizations and the institutions have intensified their actions, achieving that the States assume with greater responsibility the defense of the heritage. Cuba, as a signatory of these organizations, has perfected the legislative system. The municipality of Yara is the bearer of a rich heritage, but the municipal administration has shown insufficiency in its management due to lack of competence in patrimonial matters. This makes it impossible to promote strategies that stimulate citizen participation and local development. From this problematic the investigation proposes, as an objective, to value the viability of the juridical foundation for the management of the Cultural Patrimony, with emphasis in the citizen participation and the local development. Paying more attention to Cultural Heritage helps to be more effective in relations with the community, to understand the values of its heritage and to manage the impacts aimed at improving the well-being and quality of life of its inhabitants.